Aberrant ARID5B expression and its association with Ikaros dysfunction in acute lymphoblastic leukemia. (November 2018) - Ge, Zheng; Han, Qi; Gu, Yan; Ge, Qinyu; Ma, Jinlong; Sloane, Justin; Gao, Guofeng; Payne, Kimberly; Szekely, Laszlo; Song, Chunhua; Dovat, Sinisa
Abstract Mutations and single nucleotide polymorphisms of AT-rich interactive domain-containing protein 5B (ARID5B) are involved in the oncogenesis of acute lymphoblastic leukemia (ALL) and treatment outcomes. However, ARID5B expression and clinical significance in ALL remain unclear. We foundARID5B is significantly down-regulated in ALL compared to healthy bone marrow controls. ARID5B also interacts with PHD finger protein 2 (PHF2). Low expression ofARID5B (ARID5B low ) orARID5B andPHF2 (ARID5B low PHF2 low ) is correlated with the markers of cell proliferation and poor prognosis in ALL patients. Ikaros directly regulates ARID5B expression in ALL. Restoring Ikaros function by Casein Kinase II inhibition also promotes ARID5B expression through recruitment of trimethylation of lysine 4 on histone H3 (H3K4me3) at its promoter region. In summary, our data show that aberrant expression of ARID5B and PHF2 is related to leukemic cell proliferation and several poor prognostic markers. Our data indicate ARID5Blow expression, particularly ARID5Blow PHF2low expression, is linked to Ikaros dysfunction and involved in the oncogenic effect of high-risk ALL, which may represent a high-risk subgroup of ALL.